Social inclusion through art therapy with a focus on gender, experience with Latin American migrants - Javiera Hauser Dacer (Arteterapia)
Latin America migrant women are playing a significant role in contemporary migration movements, being integrated on their own jobs and new culture, thus helping development of both countries: origin and host societies. The proposed work is an art therapy intervention from a gender perspective carried out under the project: “Service of psychological support, psycho-pedagogical and educational for groups with special difficulties of social insertion, educational and employment”, funded by the European Social Fund and managed by the Community of Madrid and the Foundation Humanism and Democracy